2008
DOI: 10.1109/tmag.2008.2002401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of van der Waals Forces in a Near Contact Head-Disk Interface

Abstract: The minimum flying height, elastic deformation, and attractive pressure caused by van der Waals force under static air-bearing pressure were analyzed numerically using a spherical pad slider and a flat disk model. Parametric analysis revealed that when the pad radius of curvature was 20 mm, the minimum possible flying height was about 1 nm. The smallest roughness height, for reducing the van der Waals attractive force to less than the meniscus force, is 0.5 nm.Index Terms-Allowable minimum roughness, head-to-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…( 4) [19]. (4) where h is the lubricant thickness, and γ d bulk is the dispersive surface energy of bulk lubricant material (13.0 mJ/m 2 in both lubricants [19]). The coverages of both lubricant films are 90% and 91% for D-4OH and Z-tetraol, respectively Therefore, these values are uniform and extremely high; so the dissociation of Ar clusters is not affected by the location of impact.…”
Section: Lubricant Film Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…( 4) [19]. (4) where h is the lubricant thickness, and γ d bulk is the dispersive surface energy of bulk lubricant material (13.0 mJ/m 2 in both lubricants [19]). The coverages of both lubricant films are 90% and 91% for D-4OH and Z-tetraol, respectively Therefore, these values are uniform and extremely high; so the dissociation of Ar clusters is not affected by the location of impact.…”
Section: Lubricant Film Thicknessmentioning
confidence: 99%
“…Saitoh and Miyake evaluated the dynamic deformation properties of PFPE-coated magnetic disks using a force modulation method via atomic force microscopy [3]. Ono numerically analyzed the minimum flying height, elastic deformation, and attractive pressure caused by van der Waals forces under static air-bearing pressure using a spherical pad slider and a flat disk model for the HDI [4]. Their research suggested that not only the surface topography but also the mechanical properties (elastic modulus and hardness) of the surface are extremely important when considering nanometer-order contact problems.…”
Section: Introductionmentioning
confidence: 99%
“…磁気ディスク装置におけるコンタクト記録スライダは, 1997~2004 年頃浮上ヘッドスライダの浮上量のばらつ き要因をなくして浮上すきまを数 nm 以下に低減させる手段として盛んに研究された (1)-(4) が,接触振動の発生 (5) , ヘッド摩耗等によりその実現の可能性は小さかった.その後熱アクチュエータによりヘッド部を局所的に突出さ せる Thermal Flying height Control (TFC) [Dynamic Flying Height control (DFH) ともよばれる]スライダ (6) が実用 化され,各スライダの浮上すきまのバラツキが除去された.また接触面積が減ったため,潤滑剤のメニスカス力 が低下し,さらにピコスライダに代わって小形のヘムトスライダが採用されたため,激しい跳躍自励振動の発生 がなくなった (7) .TFC 技術により,現在のヘッド・媒体間浮上すきまは 2~3 nm 程度まで低減され,磁気ディス クの記録密度は 700 Gb/in 2 レベルになっている.今後さらに 1 Tb/in 2 以上の高記録密度を実現するには,1 nm 程 度の微小すきまの実現が望まれている.しかしヘッド部の等価曲率半径が 20 mm の場合でも,ヘッドとディスク の平均面間距離が 1 nm 強から吸着してしまうことが予測されている (8) .したがって今後は,平均面間すきまが 1.3 nm 程度以上の非接触記録か,平均すきま 1 nm 以下の接触記録を選択しなければならないと考えられる. このようなヘッド・ディスク間すきまの狭小化の要請から,ヘッドを潤滑膜の流動層内で滑らす, surfing-recording の概念が Liu 他 (9), (10) により提案されている.接触記録の可能性を調べるため,TFC slider で,ヘ ッド部をディスク面に接触させるタッチダウン特性に関する実験が, Canchi & bogy (11), (12) ,Ma 他 (13) ,Shimizu 他 (14) , Tani 他 (15) 等により行われている.実験で用いたヘッドスライダ,潤滑剤等の実験条件の違いにより現象は異なる が,共通している現象は,ヘッドスライダの接触開始時には接触振動が生じるが,押し込み量を増加させると安 定な接触走査が得られる領域があることである.またヘッド押し込み量を増すとスライダの振動が低周波数成分 から高周波数成分へと変化する傾向がみられる.振動が生じない押し込み量領域を広げることができれば,TFC スライダによる on demand 方式の接触記録を行える可能性がある. ヘッドスライダの近接時から接触時におけるスライダ振動特性の数値シミュレーションも,Yu 他 (16) ,Vakis 他 (17) ,Zheng & Bogy (18) 等により行われ,接触開始時は接触振動が生じるが,押し込み量を大きくすると抑圧され ることが示されている.これらのシミュレーションは,ヘッド・ディスク間の相互作用力が正しく評価されてい れば,特定のヘッドスライダの特性を説明するためには優れているが,接触振動特性の全体を概観し,振動特性 のメカニズムとそれを支配するパラメータを明らかにし,更に安定に接触滑りするコンタクトスライダの基本的 な設計法を明らかにするには不適当である.Canchi & Bogy (19) は特定の条件下でピッチ 1 次モードの振動数の 2 倍がピッチ 2 次振動数に一致すると,非線形系の内部共振により大きな振動が生じること,また接触剛性特性の 非線形による高調波共振や分数次共振が起こることを非線形振動理論に基づき解析しているが,かなり特殊な条 件下の現象であり,一般的な振動挙動は解明されていない. これに対して,飯田他 (3) および Ono (4) Head-penetration depth , Canchi & Bogy (11) , Shimizu 他 (14) ,Tani 他 (15) の実験では,touchdown 直後は,100 kHz 以下の低周波数の成分 が励起されている. 特に Laser Doppler 振動計でスライダの 3 ないし 2 方向成分を測定している Canchi & Bogy (11) , Shimizu 他 (14) では,touchdown 直後は off-track 方向に 100 kHz 以下の振動が励起され,押し込み量を大きくする にしたがい,これらの成分は小さくなっている.スライダ・サスペンション系は 100 kHz 以下の共振振動数の振…”
Section: 緒 言unclassified
“…The TFC technology has been widely used in HDD products [7], and has made a sub-2 nm FH become reality [8]. In pursuit for much higher read/write capacity, a FH of less than 0.5 nm may be required in the future [9]. To achieve this, the surfaces of the slider and the disk need to be atomically smooth.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the surfaces of the slider and the disk need to be atomically smooth. An extremely smooth slider and disk working under ultra-low FH can lead to strong adhesive interactions at the head-disk interface (HDI), which may influence the dynamic properties of the slider and the read/write capacity of the disk [4,[8][9][10]. Furthermore, the possibility of contacts between the slider and the disk increases, and, as a result, the traditional flying recording mechanism may transform to the lubricant-contact [11,12] or solid-contact [7] recording mechanisms.…”
Section: Introductionmentioning
confidence: 99%